2008
DOI: 10.1080/02678290701744579
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced gliding of the surface director in azo‐dye doped nematic liquid crystals

Abstract: We report photoinduced surface director gliding with azo dye-doped nematic liquid crystals. This gliding has the same characteristics as that induced by an applied magnetic field. Fast and slow dynamic regimes are observed, the latter fitting to a stretched exponential. In addition, the gliding demonstrates a 'sensitizing' effect for sequential measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…К наиболее перспективным методам полу-чения ориентированных ЖК относится их ориен-тирование в системах ЖК-краситель с помощью светового или лазерного излучения [2][3][4][5][6][7][8][9][10][11][12][13]. Этот эффект называется фотоориентацией.…”
Section: unclassified
“…К наиболее перспективным методам полу-чения ориентированных ЖК относится их ориен-тирование в системах ЖК-краситель с помощью светового или лазерного излучения [2][3][4][5][6][7][8][9][10][11][12][13]. Этот эффект называется фотоориентацией.…”
Section: unclassified
“…Over the past few decades this slow motion -the socalled easy axis gliding -has received much attention * Email address: kiselev@iop.kiev.ua † Email address: eechigr@ust.hk as a widespread phenomenon observed in a variety of liquid crystals on amorphous glass [3], polymer [4][5][6][7][8][9][10][11][12][13] and solid [6,11] substrates. Recently, it was found that, in addition to magnetically (electrically) induced gliding, there is the photoinduced gliding of the easy axis in dye-doped liquid crystals [14,15]. According to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists of photoinduced reorientation of the easy axis at the liquid crystal/polymer surface associated with photo-excitation and trans to cis isomerization of the dye 4,5 . In particular, it has been observed that liquid crystal samples doped with the azo dye methyl red and one surface coated with fluorinated polyvinyl cinnamate (PVCN-F) demonstrate a significant amount of reorientation of the easy axis on that surface 6,7,8 .…”
Section: Introductionmentioning
confidence: 97%
“…Our work has involved comparing the effects of various azo dyes, their interactions with polymer substrates, both rubbed and unrubbed, and the anchoring strength between these dyes and the liquid crystals. Recently, we measured photoinduced azimuthal reorientation on rubbed PI using DO3 doped nematics 5 . We have also found that this photoinduced reorientation of the easy axis involves a memory effect, consistent with the results of Ouchi, et al 13 .…”
Section: Introductionmentioning
confidence: 99%